Studi Filologis Sharh Isagoge: Menelusuri Logika Aristotelian di Kalangan Muslim Klasik - Adiwidjajanto, Koes (Program Studi Filsafat Agama Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2012)
This article puts emphasis on Daljî, one of traditional Muslim scholars, about his writing ?Ta?lîqât ?alâ Sharh Shaykh Islâm Zakarîyyâ al-Ansârî li Matn Isaghuji?, with philological approach. Such approache has been widely known in Islamic world as tahqîq al-nusûs, which focuses on presenting part of the text readable in different time and context, so it can be used and read in accordance with writer?s intention. What important from Daljî?s contribution in the study of traditional Aristotelian logic (mantiq) is that his defense on this study has firm position, whereas another Sunnî Traditionalist especially the people who was known as Ahl al-hadîth like Ibn Salâh and Ibn Taymîyya considered it as innovation according to the authoritative Islamic teachings. In his ta?lîq, Daljî followed the previous Muslim Scholar in writing logical method that was considerably known amongst its experts. The topics discussed in this study deal with explanations on kulliyât (generals), qadâyâ (prepositions), al-?aks wa al-tanâqud (the contradictions), on qiyâsât (syllogism), on rhetoric and poetics.